A template-based approach to measure supply chain flexibility: a case study of Indian soap manufacturing firm. Issue 2 (7th April 2020) - Singh, Rohit Kumar; Acharya, Padmanav; Modgil, Sachin
Abstract : Purpose: The purpose of this study is to quantify the supply chain flexibility for an Indian soap manufacturing firm and to measure its performance. The authors made an attempt to find key strategic and operational decision-making dimensions for developing effective supply chain flexibility environment. Design/methodology/approach: The authors have extracted 11 supply chain flexibility dimensions through extensive literature review. The authors used a decision-making trial and evaluation laboratory (DEMATEL) to make causal analysis and prioritizing the dimensions. After DEMATEL analysis three major supply chain flexibility dimensions that seem to have significant amount of influence on supply chain performance of the firms were retained for further consideration. The authors have developed an excel-based template for quantitative assessment of flexibility performance indicators. Findings: This study provides key enablers for the successful implementation of flexibility concepts in Indian soap manufacturing firms and gives a view how to measure the performance through designing template based on real data. This template can be used in other firms also by simply modifying the key attributes. Originality/value: A flexibility index has been defined here with the purpose of assessing the level of flexibility vis-a-vis what is desired and is meant to be evaluated from time to time, to assess if the firm is improving its flexibility or not. The index assumes importance in view of the fact that it has been prepared based on feedbacks of both the upper and the lower management people of the firm engaged in policymaking and operations.